The effects of continuous application of sunscreen on photoaged skin in Japanese elderly people – the relationship with the usage - Mizuno M; Kunimoto K; Naru E; Kameyama K; Furukawa F; Yamamoto Y (Dove Medical Press, 2016)
Makoto Mizuno,1,2 Kayo Kunimoto,1 Eiji Naru,2 Koichi Kameyama,2 Fukumi Furukawa,1 Yuki Yamamoto1,3 1Department of Dermatology, Wakayama Medical University, Wakayama, Japan; 2Fundamental Research Laboratories, KOSÉ Corporation, Tokyo, Japan; 3Department of Cosmetic Dermatology and Photomedicine, Wakayama Medical University, Wakayama, Japan Abstract: Since photoaging of skin is caused by chronic sun exposure, it is well-recognized that regular sunscreen use can help prevent photoaging of skin in fair-skinned people. Therefore, application of sunscreen is recommended for the prevention of photoaging in many countries. However, the relationship between UV exposure and photoaging has rarely been investigated in clinical studies in Japan. In addition, there have been almost no long-term interventional studies in Japanese people. We have previously conducted a study where Japanese actinic keratosis patients were instructed to continuously apply sunscreen. The results indicated that long-term application of sunscreen is effective in suppressing actinic keratosis progression and generation. In the present study, we investigated the effects of sunscreen on photoaged skin in 14 elderly Japanese people. Skin conditions such as water content, transepidermal water loss, the number of spots, wrinkles, and skin color tone uniformity were measured and compared before and after the study. A statistically significant difference was observed only in skin surface hydration. There were large inter-individual differences in amount of sunscreen used throughout the study. The changes in the number of spots and skin color tone uniformity during the 18 months showed good correlation with amount of sunscreen being used. These results suggest an increase in the number of spots and deterioration in skin color tone uniformity in the 18-month non-sunscreen application period, and that such skin conditions improved with increasing use of sunscreen. In this study, we suggested an inhibitory effect on photoaging symptoms such as spots and skin color tone non-uniformity, by application of the appropriate amount of sunscreen over a long period of time in Japanese people, similar to Caucasians. Keywords: UV, prevention, spot, wrinkle, skin color tone, moisturizing